The impact of regular physical exercise on mobile phone addiction tendency among Chinese college students: the mediating role of trait boredom and the moderating role of self-control - Qi, Jiatian; Zhou, Xiaoyou; Li, Jingjing; Liu, Bing (Frontiers in Psychology, 2025)
IntroductionThis study explores the relationship between regular physical exercise and mobile phone addiction tendency among college students, with a focus on the mediating role of trait boredom and the moderating role of self-control.MethodsA total of 560 students from three universities in Shanghai were surveyed using the Revised Physical Activity Rating Scale, the Exercise Stage Scale, the Trait Boredom Scale, the Brief Self-control Scale, and the College Students’ Mobile Phone Addiction Tendency Scale.Results(1) regular physical exercise is significantly negatively correlated with mobile phone addiction tendency, suggesting that students who engage in more regular physical exercise exhibit lower levels of mobile phone addiction tendency; (2) trait boredom mediates the relationship between regular physical exercise and mobile phone addiction tendency; (3) self-control moderates the effect of trait boredom on mobile phone addiction tendency, such that higher levels of self-control weaken the positive association between trait boredom and mobile phone addiction tendency, whereas lower levels of self-control strengthen this association; (4) the moderating effect of self-control on the direct relationship between regular physical exercise and mobile phone addiction tendency is not significant.DiscussionThis study reveals the underlying mechanisms through which regular physical exercise affects mobile phone addiction tendency and provides theoretical and practical implications for the design of intervention strategies and the cultivation of self-control among college students.